Innovative ICT platforms: the Indian experience. (19th July 2005) - Bowonder, B.; Mastakar, Nrupesh; Sharma, K.J.
Information and Communication Technology has been used traditionally by industries. ICT could help in improving governance at various levels. The paper summarises the findings of a series of ICT initiatives taken in India. The detailed case studies presented in the subsequent papers in this issue clearly shows that application of ICT could provide substantial benefit to traditional societies. The poorer sections of society could easily get access through the newer options that are available. The success of implementation of ICT projects depends on social and psychological readiness of the beneficiaries for accepting change. Another critical success factor of the ICT projects is the nature of the beneficiary involvement in the design and delivery of the proposed system.